Essays on typology - Lampe, G.W.H.; Woollcombe, K.J. (Naperville, IL Alec R. Allenson, 1957)
Contents : The Reasonableness of typology by G.W.H. Lampe; The biblical origins and patristic development of typology by K.J. Woollcombe. Includes bibliographical references and indexes.
Donated from the library of Mr John Fraser Dickson, November, 2002.
Keywords: Bible -- typology